Skin Autofluorescence and Carotid Intima-Media Thickness Evaluation Following Bariatric Surgery in Patients with Severe Obesity - YAVUZ, DİLEK (SPRINGER, 2021)
Purpose Advanced glycation end product (AGE) is a marker of metabolic memory. Accumulated AGEs in skin collagen measured with skin autofluorescence (SAF) was found to be associated with subclinical atherosclerosis. We aimed to evaluate SAF and carotid intima-media thickness (CIMT) and its association with clinical and biochemical parameters in severely obese patients before and after bariatric surgery. Materials and Methods In this observational study, 432 morbid obese patients evaluated before and after 6 and 12 months of bariatric surgery for metabolic and anthropometric parameters, CIMT and SAF. SAF was assessed in the forearm with an AGE Reader. Results SAF measurements were higher in diabetic (2.04 +/- 0.52 AU) obese patients compared to non-diabetic (1.78 +/- 0.40 AU) obese patients (p < 0.0001). Although bariatric surgery-induced weight loss resulted in a decrease in CIMT in the 6th and 12th months compared to baseline, weight loss and metabolic improvements were not associated with a parallel decrease in SAF measurements. SAF measurements were positively correlated with body mass index (r 0.527, p < 0.0001), HbA1c (r 0.362, p < 0.0001), and CIMT (r 0.319, p < 0.0001). Multivariate analysis showed the presence of diabetes (but not BMI, age, and sex) was independently associated with SAF (R-2 = 7.62%), and the presence of diabetes, low-density cholesterol, and systolic blood pressure were independently associated with CIMT measurements (R-2 = 21.7%). Conclusion Bariatric surgery-induced weight loss and metabolic improvement were found to be associated with improvement in CIMT, while skin AGE accumulation was not regressed in the first year of surgery.
Keywords: Advanced glycation end products; Bariatric surgery; Carotid intima-media thickness; Obesity; Type 2 diabetes; Skin autofluorescence; GLYCATION END-PRODUCTS; NONINVASIVE MARKER; MORBID-OBESITY; ATHEROSCLEROSIS; MANAGEMENT; MORTALITY; STRESS; RISK